Hypertrophic muscle changes and sprint performance enhancement during a sprint-based training macrocycle in national-level sprinters - Nuell, S.; Illera-Dominguez, V. R.; Carmona, G.; Alomar, X.; Padullés, J. M.; Lloret, M.; Cadefau, J. A. (European Journal of Sport Science, 2020)
This study aimed to analyse changes in sprint performance, muscle volumes (MVs) and sprint mechanical parameters (SMPs) in national-level sprinters performing a 5-month indoor sprint-based training macrocycle (SBTM). Twelve well-trained sprinters were tested on three different occasions throughout the SBTM. Testing procedures included: sprint performance over 10m, 40m, 80m, 150m, and 300m; MRI of thighs, to compute MVs of quadriceps, hamstrings and adductors; and a 40m sprint using a radar gun to assess SMPs such as theoretical maximal horizontal force, theoretical maximal horizontal velocity (V0), maximal power and index of force application (DRF). Improvements in sprint performance of between 4% and 7% (ES = 0.46-1.11, P < 0.01) were accompanied by increments in: quadriceps of 6% (ES = 0.41, P < 0.01), hamstrings of 10% (ES = 0.62, P < 0.01), adductors of 12% (ES = 0.87, P < 0.01), V0 of 5% (ES = 0.40, P < 0.01) and DRF of 7% (ES = 0.91, P < 0.01). In conclusion, during the SBTM after the off-season, moderate hypertrophic changes occur in sprinters. Moreover, the greater increase in hamstrings and adductors, compared with quadriceps, might be related to the prominent role of these muscle groups in sprinting. Furthermore, the SBTM was likely effective at developing sprint performance in sprinters, thereby endorsing the idea that sprint-specific training is crucial for highly trained individuals. Finally, our results support the notion that V0 or the "velocity-oriented" force-velocity profile is determinant of performance in sprinters.